Pengembangan LKPD Discovery Learning untuk Menanamkan Pendidikan Karakter Siswa Kelas V Sekecamatan Jatinom Tahun Pelajaran 2023/2024 - Linda Apriyani; Ronggo Warsito; Isna Rahmawati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research is motivated by the fact that the implementation of character education in schools has not been implemented optimally in the learning process. The need for developing student worksheets that are integrated with character education aims to establish student cooperation, activeness, independence, discipline and responsibility. The type of research used is research and development, also called R&D (Research and Development), using the Borg and Gall model, carried out in 6 stages. The validation results obtained from this research were that material experts received 93.18% (very worthy), media expert validation 87.5% (very worthy), and practitioner expert validation 84.1% (very worthy). The practicality of the LKPD obtained at SD Negeri 1 Mranggen had an average score of 88.66% (very practical), SD Negeri 2 Gedaren 89.16% (very practical) and SD N 2 Mranggen 87.83% (very practical). The value before product application and after product application experienced a significant increase with an N-gain score of 58.42% (quite effective). The results of this development research show that the discovery learning LKPD is feasible, practical and quite effective when used.